ANALISA PENGARUH PERCEIVED SERVICE QUALITY TERHADAP CUSTOMER SATISFACTION DENGAN CUSTOMER VALUE SEBAGAI VARIABEL INTERVENING PADA PROGRAM MANAJEMEN PEMASARAN UNIVERSITAS KRISTEN PETRA - Kevin Tanjaya (Jurnal Strategi Pemasaran, 2016)
College is an educational institution that has various departments which are capable of forming ability of students before having working experience. Students choose majors connected to work that will be taken after college. Marketing Management Program is one of the majors offered from economic faculty that focus on selling and development of products or brands. Student satisfaction on the quality of service is the main thing that must be maintained at all universities, students' expectations to a department one of which comes from word of mouth that can trigger value or the value of the majors. Any student who is satisfied will most likely give recommendation to others. Hence the need to evaluate the quality of service in creating value and satisfaction of students.